Unveiling trends and clinical progress of immunotherapy for endometrial cancer: a scientometric and clinical trial landscape analysis - Liu, Ruoyan; Shan, Wenhui; Hu, Zhuopeng; Wang, Hong; Wang, Zhening; Yang, Lei; Guo, Rui (Frontiers in Immunology, 2026)
BackgroundEndometrial cancer (EC) is a heterogeneous and increasingly prevalent malignancy characterized by distinct molecular subgroups that exhibit fundamentally different immune profiles. These immunologic differences shape tumor–immune interactions, influence responsiveness to immunotherapy, and underscore the importance of biologically informed treatment strategies. As the clinical application of immune checkpoint inhibitors expands, understanding the mechanistic and translational landscape of immunotherapy in EC has become essential for guiding precision oncology.MethodsWe systematically retrieved 836 immunotherapy-related publications on EC from the Web of Science Core Collection (1999–2024) and conducted a scientometric analysis using VOSviewer and CiteSpace. Analyses included publication trends, country and institutional collaborations, author networks, and keyword clustering. Furthermore, we screened 391 clinical trials from ClinicalTrials.gov and ICTRP databases to assess the clinical research landscape.ResultsPublication output and clinical trials on EC immunotherapy have shown a continuous upward trend over the past two decades. The United States and China emerged as leading contributors in both publications and pivotal clinical trials. Among the most frequently co-cited references, clinical studies account for a significant proportion, particularly those published in the last five years. The landscape reflects a shift toward immune checkpoint blockade and combination therapy strategies, with some clinical trials demonstrating promising efficacy.ConclusionOur integrated scientometric and clinical trial analysis reveals a rapid evolution in EC immunotherapy research, highlighting checkpoint blockade as a central therapeutic approach. The trend toward combination regimens underscores the translational potential of immunotherapy in EC and points toward emerging directions for future research and clinical application.